2019
DOI: 10.1007/s13202-019-0689-7
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide/carbon nanotubes nanocoating for improved scale inhibitor adsorption ability onto rock formation

Abstract: The formation of mineral scale has been a major constraint in the oilfield operations as it leads to numerous flow assurance issues. Scale deposition in the formation and production tubing can restrict the flow of hydrocarbon and interferes with the running and operation of downhole equipment. Scale inhibition squeeze treatment is one of the most common form of scale prevention. Although current squeeze treatment is the optimal way to prevent scale from depositing, it is still lack in certain aspect such as ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…[ 42 ] Another study demonstrated that using nanomaterials like CNT and GO in a brine that contains calcium ions can improve the SI adsorption more than DW, but the SI concentration reduction at their ideal experiment (83%) is lower than the optimal condition of this study (93%). [ 44 ] As a result, the ideal scenario for improving scale inhibitor adsorption is to eliminate monovalent cations from SW that may block the adsorbent's surface active sites and keep the divalent cations (both Mg 2+ and Ca 2+ ). The second‐best strategy for obtaining a high scale inhibitor adsorption quantity is to use DW.…”
Section: Resultsmentioning
confidence: 99%
“…[ 42 ] Another study demonstrated that using nanomaterials like CNT and GO in a brine that contains calcium ions can improve the SI adsorption more than DW, but the SI concentration reduction at their ideal experiment (83%) is lower than the optimal condition of this study (93%). [ 44 ] As a result, the ideal scenario for improving scale inhibitor adsorption is to eliminate monovalent cations from SW that may block the adsorbent's surface active sites and keep the divalent cations (both Mg 2+ and Ca 2+ ). The second‐best strategy for obtaining a high scale inhibitor adsorption quantity is to use DW.…”
Section: Resultsmentioning
confidence: 99%
“…Scale Inhibitor Concentration Measurements. Scale inhibitor concentration was measured via ultraviolet (UV)−visible (vis) spectroscopy (note that UV−vis provides reliable and accurate concentration measurements for scale inhibitors 44 ). Thus, a Shimadzu double beam UV-1900 UV− vis spectrophotometer and a wavelength between 1100 and 190 nm was used to measure DTPMP (scale inhibitor used in this study) concentration in the adsorption and desorption tests.…”
Section: Mechanical and Thermal Tests 23a Proppant Crushmentioning
confidence: 99%
“…Significant improvement was achieved as scale inhibitor adsorption increased by 180% (when compared to the nonmodified near-wellbore surface). Moreover, Ishtiaq et al 31 introduced a new enhancement process 'Nanocarbon Enhanced Squeeze Treatment (NCEST)', in which they used graphene oxide (GO) nanomaterial to increase the active surface area for efficient adsorption of the scale inhibitor onto the rock surface; indeed, GO exhibited a maximum adsorption capacity (of scale inhibitors) of 180 mg/g (compare this to the 52 mg/g achieved by the nontreated sample). Thus, it can be concluded that the application of nanomaterials can play a vital role in enhancing scale inhibitor adsorption and improve recovery from tight formations.…”
Section: Introductionmentioning
confidence: 99%
“…Also, for the injection of cellulose solution, there are four possibilities that can take place depending on the size of the cellulose particles, the size of the pore throat and the salinity of the solution [16]. In general, nanotechnology is showing a promising and efficient tool for improving squeeze treatment lifetime along with other different areas in the oil and gas industry [17] as well as decreasing the overall cost of the squeeze treatment process by more 50% [18].…”
Section: Nanotechnology Application For Scale Inhibitionmentioning
confidence: 99%